2021
DOI: 10.1158/0008-5472.can-21-0259
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine GMCSF Signaling Contributes to Growth of HER2+ Breast Leptomeningeal Carcinomatosis

Abstract: Leptomeningeal carcinomatosis (LC) occurs when tumor cells spread to the cerebrospinal fluid–containing leptomeninges surrounding the brain and spinal cord. LC is an ominous complication of cancer with a dire prognosis. Although any malignancy can spread to the leptomeninges, breast cancer, particularly the HER2+ subtype, is its most common origin. HER2+ breast LC (HER2+ LC) remains incurable, with few treatment options, and the molecular mechanisms underlying proliferation of HER2+ breast cancer cells in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…This study was carried out in compliance with the ARRIVE guidelines. All NOD- scid IL2Rgamma null (NOD/SCID) mouse studies were approved by the COH Institutional Animal Care and Use Committee (protocol #10044) 98 and carried out in accordance with the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
“…This study was carried out in compliance with the ARRIVE guidelines. All NOD- scid IL2Rgamma null (NOD/SCID) mouse studies were approved by the COH Institutional Animal Care and Use Committee (protocol #10044) 98 and carried out in accordance with the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
“…In parenchymal metastasis, tumor cells enter the parenchyma through the endothelium surrounding the vasculature and the connected astrocytes, thereby causing perivascular proliferation [ 20 22 ]. In LM, tumor cells enter the CSF compartment and adhere to the pia mater surrounding the brain and spinal cord [ 2 , 8 , 23 25 ]. As revealed by histopathological analysis, our xenograft model demonstrated two major subtypes of CNS-metastatic cells: (1) tumor cells adhered to the blood–brain barrier and (2) tumor cells colonized the pia mater in the entire brain section (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LM is diagnosed among 1–15% of patients with systemic malignancies such as breast cancer (BC), particularly triple-negative breast cancer (TNBC) with characteristics of LM [ 1 , 3 , 4 ]. Currently, patients with LM exhibit poor clinical outcomes, including cognitive disorders and poor likelihood of survival (less than 1 year), and therapeutic strategies are limited [ 5 8 ]. Clinical studies have demonstrated that compared with systemic treatment alone, in a randomized phase III trial, intrathecal liposomal cytarabine combined with systemic treatment improved progression-free survival among patients with LM in BC [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was demonstrated by the Jandial group that the cytokine Granulocyte-Macrophage Colony Stimulating Factor (GM-CSF) plays a major role in the establishment of LM from HER2+ breast cancer. Indeed, when they inhibited GM-CSF with anti-GM-CSF antibodies combined with pan-Aurora kinase inhibitor (CCT137690), they reduced HER2+ LM cell growth in vivo [ 79 ]. Similarly, when they used the JIB04 treatment, which is a selective inhibitor of Jumonji demethylases overexpressed in their LM cell lines, they observed a downregulation of GM-CSF expression that prevents cancer cell proliferation [ 80 ].…”
Section: Development Of Brain and Leptomeningeal Metastasesmentioning
confidence: 99%